Factors that Increase Work Productivity of Civil Servant at the Dinas Perdagangan Kota Makassar - Nasir, Munawir; Syahnur, Muh Haerdiansyah (Jurnal Analisis Bisnis Ekonomi, 2021)
The effect of providing income improvement allowances, work discipline, and responsibility on increasing the work productivity of civil servants at the Dinas Perdagangan Kota Makassar is discussed in this study. This research approach uses quantitative data analysis. This study relied on primary data gathered through questionnaires. This study's sample consists of 61 people from the civil servants at the Dinas Perdagangan Kota Makassar. A questionnaire is used to collect data. Data analysis using the Structural Equation Model (SEM) or Partial Least Squares (PLS). The PLS evaluation model is carried out by evaluating both the outer and inner models. According to the findings of this study, the variable of income improvement allowance has a positive and significant effect on increasing work productivity, the variable of work discipline has no positive and significant effect on increasing work productivity, and responsibility has a positive and significant effect on increasing work productivity.